Measurement of the Bs0 production cross section with Bs0→J/ψ Decays in pp collisions at √s=7TeV - Chatrchyan, S. (2011)
The Bs0 differential production cross section is measured as functions of the transverse momentum and rapidity in pp collisions at √s=7TeV, using the Bs0→J/ψ decay, and compared with predictions based on perturbative QCD calculations at next-to-leading order. The data sample, collected by the CMS experiment at the LHC, corresponds to an integrated luminosity of 40pb -1. The Bs0 is reconstructed from the decays J/ ψ→μ+μ- and →K+K -. The integrated Bs0 cross section times Bs0→J/ψ branching fraction in the range 8<pTB<50GeV/c and |yB|<2.4 is measured to be 6.9±0.6±0.6nb, where the first uncertainty is statistical and the second is systematic. © 2011 CERN. Published by the American Physical Society under the terms of the Creative Commons Attribution 3.0 License. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.